Cheek support affects lung mechanics measurements of tidal-based spontaneous breathing. (September 2020) - Howe, S.L.; März, M.; Pinter, J.; Krüger-Ziolek, S.; Pretty, C.; Shaw, G.M.; Desaive, T.; Möller, K.; Chase, J.G.
Highlights: Lung elastance, airway resistance, and viscoelastic lung mechanics measurements are reduced when cheek support inadequate. Variation of lung mechanics measurements unaffected by level of cheek support. No rule-of-thumb able to correct for missing cheek support in lung function tests. Abstract: Background and Objective: Patients are required to support their cheeks during breath-occluding lung function tests. This prevents cheek expansion which would alter pressure measured at the mouth, and, consequently, lung mechanics measurements. To date, the effect of cheek support on airway resistance measurements has been assessed. However other lung mechanics have not been studied as thoroughly, and no algorithm to account for the effect of missing cheek support on lung mechanics measurements has been developed. Methods: Lung mechanics were assessed with a breath occlusion test during light panting in healthy subjects with and without cheek support in a body plethysmograph. Average model-based airway resistance, lung elastance, and a parameter representing the viscoelastic were measured. Results were compared to quantify the effect of cheek support on these three parameters. Results: In the nine healthy subjects (5 Female, 4 Male) recruited for this study, all mechanics tended to be underestimated when cheeks were unsupported. Changes in elastance, resistance, and viscoelastic parameter ranged between 1.6–66.8 %, -4.5–21.8 %, and -4.7–68.2 %, respectively, when cheek support was added. The underestimation was due to reduced mouth pressure during cheek expansion when the breath was occluded. The variance of lung mechanics parameters did not change with cheek support in all subjects. Conclusions: The error in lung mechanics measurement caused by unsupported cheeks was subject dependent. Hence, no rule-of-thumb could be identified to reconstruct missing cheek support. For correct lung mechanics measurements during breath-occluding lung tests, patients must have adequate cheek support. Abbreviations: ROCC: Occlusion resistance; COPD: Chronic Obstructive Pulmonary Disorder; SB: spontaneous breathing.